Supporting Jamu Entrepreneurs: Innovative Financial Record-Keeping Solutions for Karya Jaya Village - Yunita Sarah Siregar; Wina Nurfitriani; Lailan Syafrina Hasibuan; Syafrita Ridha Ginting (Yayasan Literasi Sains Indonesia, 2026)
This community service program aimed to enhance the digital financial literacy of traditional jamu sellers in Karya Jaya Village, Rambutan District, Tebing Tinggi City, through the implementation of a structured training and mentoring model. The program was designed using a participatory approach that integrated needs assessment, classroom instruction, hands-on workshops, and post-training mentoring. Initial field observations revealed that most participants relied on memory-based or manual bookkeeping practices, resulting in inaccurate financial records, difficulty separating personal and business finances, and limited ability to evaluate profitability. Training sessions introduced participants to user-friendly digital bookkeeping applications, particularly VoCash, focusing on cash flow recording, expense categorization, financial separation, and preparation of basic financial reports. Evaluation using pre-test and post-test instruments demonstrated an average increase of 45% in participants’ financial knowledge and digital competency. Furthermore, 85% of participants reported being able to independently record transactions after the mentoring phase. Beyond technical improvements, the program fostered behavioral changes in financial discipline and transparency. The findings indicate that community-based digital literacy interventions can significantly strengthen micro-entrepreneurs’ financial management capacity and support sustainable local economic development.